Recurrent Canine Paraphimosis: Modified Surgical Approach - de Souza, Hudimila Dutra Mascarenhas; Franco, Guilherme Galhardo; Corato, Gabriela Fiuza; Neto, José Aloizio Gonçalves [UNESP]; de Oliveira, Leticia Leal (My University, 2021)
Background: Paraphimosis is characterized by persistent penile exposure, due to the inability to retract the penis into the prepuce. This persistent exposure of a non-erect penis might result from traumas, infections, neoplasia, anatomic or neurological alterations, or even occur in its idiopathic form. Surgical treatment is indicated when it is not possible to keep the penis covered by the foreskin by trying it manually. The surgical techniques described are efficient in small exposures, however, when these are over 1.5 cm, surgical success might become a challenge. The objective of this study is to report a modified surgical approach to solve a 5 cm recurrent paraphimosis in a dog. Case: A 1-year-old male unneutered mixed-breed dog, weighing 26 kg, was presented for examination with a history persistent paraphimosis background for around 2 months without apparent cause. The animal's tutor reported that it had been submitted to 2 unsuccessful surgical procedures. When the reproductive system was examined, the animal showed a flaccid penis with 5 cm exposure outside the foreskin. A conservative treatment was used, which was also unsuccessful. The next step was a surgical procedure that used the combination of techniques, namely, phallopexy, preputial advancement and reconstruction preputial opening with suture along with orchiectomy. After 10 days, dehiscence of the ostium stitches occurred, which required debridement and new suture. However, it was not efficient and recurrence of the paraphimosis was observed. After 1 month, a new surgery was performed by adapting the phallopexy technique, which was carried out bilaterally and associated to the reconstruction preputial opening with captonated suture, which presented a successful outcome. After 8 months as of the last procedure, the patient is healthy and has no signs of paraphimosis recurrence. Discussion: No consensus has been achieved regarding the paraphimosis treatment, and the resolution of such disorder remains a challenge. For this reason, some parameters should be considered to minimize failure when choosing the surgical technique and, consequently, the recurrence of such condition. Tissue viability, morphological alterations, time of exposure, previous surgeries, and the length of the penis exposure are some of the criteria that must be taken into consideration when choosing the surgical technique. In this case, the first choice was the association of techniques that included preputial advancement, phallopexy and suture preputial opening due to the fact that the exposure was over 1.5 cm and for the existence of a preputial ostium defect, which justified its suture. Despite these associations, paraphimosis recurrence was observed and some of the probable causes include the inadequate position of the penis inside the foreskin flap during the phallopexy and lack of preputial integrity in its ventral aspect. The preputial advancement performed was not sufficient to prevent the exposure or reduce it in the recurrence of the condition, showing that the shortening of preputial muscles and the skin tension might loosen up with time. The second surgery employed bilateral phallopexy without penis exposure to guarantee its correct position, more caudal within the foreskin at the moment of the fixation. The ostium captonated suture also had a relevant role in the tension distribution up to the full tissue healing. New surgical approaches might be needed to achieve success in the paraphimosis treatment. In this report, the length of the penis exposure and the ostium defect were complicating factors. However, the association of the modified surgical techniques resulted in a successful resolution of the condition.
Parafimose canina recidivante: abordagem cirúrgica modificada
Keywords: Penis; Phallopexy; Prepuce; Preputial advancement